ANALISIS PENDAPATAN USAHATANI KOPI LIBERIKA (Coffea liberica) DI KECAMATAN RANGSANG PESISIR KABUPATEN KEPULAUAN MERANTI - Fadli, Muhammad; Bakce, Djaimi; Muwardi, Didi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Rangsang Pesisir District is the center of Liberika coffee plantation in Kepulauan Meranti Regency. Liberika coffee plantations in Rangsang Pesisir District are cultivated using cultivation techniques that they employ are intercropping cultivation techniques with coconut plants. The coconut plant is a shade crop for the Liberika coffee plant. The purpose of this study was to determine the application of cultivation techniques and analyze the income of Liberika coffee farming. The method used is descriptive analysis and farm income analysis. The respondents consisted of 30 Liberika coffee farmers. The results of the analysis of the Liberika coffee cultivation technique show that the Liberika coffee cultivation technique in the Rangsang Pesisir sub-district is not in accordance with the recommendations, while the Liberika coffee farming revenue shows a total profit of IDR 7,119,227.92 per ha per year.Keywords: Liberika Coffee, Income Analysis, Cultivation Techniques.